EDUKASI HYDROTERAPI WUDHU SISWA PENDIDIKAN VOKASI - Dian Cita Sari; Ayu Permata (LPPM IKIP Jember, 2018)
The influence of wudu is so deep that wudu can cultivate positive perception and motivation, effective coping, positive emotional response, and can avoid stress reaction. Body part that is exposed to ablution water is an open body part, which is often encountered by bacteria and virus causing disease, that part must be cleaned to avoid various diseases .. For that, Hydroterapi education ablution on vocational education students is an integrated mental education program that serves as a key learning. This is a solution to improve learning success for children who choose vocational education as a means of aspiration towards the future. However, the devotion to the mental education program for vocational education students based on school health units is still very limited. Therefore, it takes a dedication that can produce technical applications. Location devotion is in SMKN 2 Pekanbaru. This devotion is motivated by mental readiness in low vocational student learning. One reason is that the students feel very anxious, and frightened when confronted with technical things outside of themselves. Solutions that can be done to reduce anxiety or stress in the face of learning is to perform ablution before the class begins.